Feminicídio: análise da aplicabilidade da lei 13.104 de 09 de março de 2015 no município de Mossoró-RN - Silva, Simony Pereira Alves da (Universidade Federal Rural do Semi-Árido, 2018)
This article presents a survey of statistical data on the applicability of the qualifier in crimes of feminicide, in the city of Mossoró-RN. The research has a quantitative and qualitative character, between the years 2015 to 2018. Ten (10) cases of femicide were found next to the 1st Criminal Court of the present city two (2) cases were filed, two (2) were judged, and six (6) are in progress for trial, in which gender violence was identified, resulting in death and application of Law 13,104 of March 9, 2015 in the municipality. For this, we used the technique descriptive analysis in order to distinguish crime. In the analysis of the data collected, it was verified that all cases of femicide occurring in the family settings the victim had affective relations with the authors. It is concluded that femicide, are deaths that could be avoided. Violence against women has a cultural background, the motivation of crime and the "condition" of women, especially in cases of intimate femicide. In order to prevent violence in the aforementioned city, a number of public policies have been instituted to protect women victims of violence, in particular there are two municipal laws that encourage women who are victims of violence and denounce perpetrators before femicide occurs. Gender-based violence needs to be addressed primarily through public policies.
Artigo Acadêmico
Keywords: Feminicidio; Cidade de Mossoró- RN; Politicas publicas; Homicídio contra mulher; Qualificadora; Lei 13.104 de 2015; Feminicide; City of Mossoró- RN; Public policy; Homicide against woman; Qualifier; Law 13,104 of 2015; CIENCIAS SOCIAIS APLICADAS::DIREITO